2019
DOI: 10.1016/j.scitotenv.2018.10.289
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 52 pesticides in fresh fish muscle by QuEChERS extraction followed by LC-MS/MS determination

Abstract: Pesticide pollution in water has been well described; however, little is known on pesticide accumulation by aquatic organisms, and to date, most studies in this line have been focused on persistent organochlorine pesticides. For this reason, a method based on QuEChERS extraction and subsequent liquid chromatography-tandem mass spectrometry (LC-MS/MS) has been developed and validated for the determination of 52 medium to highly polar pesticides in fresh fish muscle. Target pesticides were selected on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 24 publications
5
29
0
4
Order By: Relevance
“…Lately, these chemicals have been found in different matrices, including dietary products, water, outdoor and indoor air and house dust (Banerjee et al, 2012;Sousa et al, 2018;Coscollà et al, 2017;Gibbs et al, 2017;Mercier et al, 2011;Tang et al, 2018). In addition, recent studies have found them even in freshwater and edible fish (Arisekar et al, 2019;Barbieri et al, 2019;Pico et al, 2019), being in some cases related with pollution accidents, like the death fish episode by pyrethroid exposure in Northern Italy (Bille et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, these chemicals have been found in different matrices, including dietary products, water, outdoor and indoor air and house dust (Banerjee et al, 2012;Sousa et al, 2018;Coscollà et al, 2017;Gibbs et al, 2017;Mercier et al, 2011;Tang et al, 2018). In addition, recent studies have found them even in freshwater and edible fish (Arisekar et al, 2019;Barbieri et al, 2019;Pico et al, 2019), being in some cases related with pollution accidents, like the death fish episode by pyrethroid exposure in Northern Italy (Bille et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the addition of salt leads to a decrease in the solubility of the analytes in the aqueous phase and enhances the extraction efficiencies. 8,31 In this study, by increasing the NaCl amount, the peaks areas were decreased. Hence, no salt was added in the subsequent experiments.…”
Section: Effect Of Salt Concentrationmentioning
confidence: 53%
“…At a pH higher than 6, the peak areas decreased, due to the hydrolysis of the pesticides. 8 Therefore, the pH of the sample solution should not exceed 6. Considering that the pH values of the investigated fruit juice samples were below 6, 29 the experiments were carried out without pH adjustment.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Current agriculture has been studied continuously using organic pesticides to produce improved crop yields and food health (Aswathi et al, 2019). While pesticides play an important role in the growth of crops in modern agriculture, widespread use does significant harm to the environment (Barbieri et al, 2019). The use of organophosphorus pesticides (OPs) have triggered alarm over environmental pollution, food safety and contact toxicity.…”
Section: Introductionmentioning
confidence: 99%